If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2(-10c + 6) + 3(5 + -8) = 0 Reorder the terms: 8 + 2(6 + -10c) + 3(5 + -8) = 0 8 + (6 * 2 + -10c * 2) + 3(5 + -8) = 0 8 + (12 + -20c) + 3(5 + -8) = 0 Combine like terms: 5 + -8 = -3 8 + 12 + -20c + 3(-3) = 0 Multiply 3 * -3 8 + 12 + -20c + -9 = 0 Reorder the terms: 8 + 12 + -9 + -20c = 0 Combine like terms: 8 + 12 = 20 20 + -9 + -20c = 0 Combine like terms: 20 + -9 = 11 11 + -20c = 0 Solving 11 + -20c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -20c = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -20c = 0 + -11 -20c = 0 + -11 Combine like terms: 0 + -11 = -11 -20c = -11 Divide each side by '-20'. c = 0.55 Simplifying c = 0.55
| 35x^2-20x-55= | | h(x)=3.5-3/4x | | 5y-4=62-6y | | f(x)=4x^2+16x+13 | | 200x+1=250x | | f(-2)=4+6+1 | | 7(3y+6)= | | 7(3+6)= | | b+4=2h-5 | | 5(b-2)=30 | | 4s+35=1 | | 9x+14=2x-17 | | -4q-10=-4q+10 | | 2.11+y=1.7 | | 5b-2b-8b= | | -4=2-14 | | 3h=37 | | .5(5-2x)=x/2 | | -5(-10+6q)=-3(10q+3) | | 2z-9=33 | | 3n+3=22 | | 6r+4s=2r+8 | | 2(8-2k)+12=-12 | | a^4-18a=-81 | | 13=2p+7 | | (3x^2-7x-3)-(2x^2+1)=x^2+11 | | 2(z-2)=7z+1 | | d/3-5=3 | | (-6)(12/9)= | | 18x-42x^2=0 | | 7.3x=-35.77 | | 28=-8u+4(u+2) |